SKARIFIKASI FISIK BENIH DAN BERBAGAI MEDIA TANAM TERHADAP VIGOR MORINGA OLEIFERA - - Ubaidillah; A. V. Zulaiha; R. Dianita (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2020)
This experiment was aimed to reveal the effect of seed physical scarification and various growing mediaon vigor of Moringa oleifera. This study was conducted in greenhouse and consisted of two phases ofexperiment; first was studied the effect of physical scarification on seed germination of M. oleifera and thesecond was studied the effect of seed physical scarification and various sub optimum growing media onvigor of M. oleifera. The germination test was arranged in randomized completely design with 4 treatmentsthat were P0 = non scarification, P1 = one side scarification, P2 = two sides scarification, and P3 = full sidescarification. The variables measured were germination percentage (%) and seedling dry weight (g/plant).The second study was arranged in a factorial randomized completely design with the four treatments ofscarification (P0, P1, P2 and P3) over six growing media (sands, bricks, bricks and sands mixture, bricksand soils mixture, soils and sands mixture, and soils). The variables observed were petioles number, plantheight (cm/plant), and plant dry weight (g/plant). The scarification was significantly affect (P<0.05) thegermination percentage and seedling dry weight. Scarification and growing media also affected the vigorof M. oleifera significantly (P<0.05). Two side seed scarification improve the germination and seedling dryweight instead of control. Combination of scarification in two sides and growing media of soils and sandsmixture given the highest vigor of M. oleifera reflected on petioles number, plant height, and plant dry weight. Keywords: germination, M. oleifera, scarification, sub optimum media, vigor